Musical analysis and context in indigenous music: the poetics of the flutes. (Revista Argentina de Musicología, 2018)
We discuss here the need of a musical analysis open to the context of its object. The basis for that is the investigation of a repertoire of Indigenous music in which there are sophisticated hidden musical operations and a poetic character. instead of what is considered to be mere repetitivity. I will examine the instrumental music of the sacred flutes ritual of the Wauja Indians, inhabitants of Central Brazil's upper Xingu region. This music is a system in which the motivic dimension and variational principles are the core not only of the music but of the whole ritual, which in turn is deeply rooted in the native worldview. The musical analysis of the repertoire required the creation of a special model and revealed elegant operations of motivic repetition and differentiation, all constituting a play of ideas, a kind of artistic manipulation of pre-established gestalts, or perhaps, a poetic procedure.
Keywords: musical analysis; Indigenous flute music; motivic repetition and difference